Use of Instructional Materials for Teaching Social Studies - Yadav, Binod Kumar (Orchid Academia Siraha, 2023)
Instructional materials are both human and non-human resources used in teaching and learning activities. Social studies is an integrated subject that encompasses various subjects, such as economic, social, and cultural activities, but this subject can effectively be taught by using instructional materials. The main purpose of this paper is to enlist and describe various instructional materials used while teaching social studies in the classroom. The study was descriptive in nature. Secondary sources such as reports, books, journals, magazines and articles were used to achieve purposes of the study. Textbooks, magazines, newspaper, table, graphs, maps, radio, television are the instructional materials used during teaching social studies. Social studies are centered to old tradition in their teaching-learning activities. As social studies subject is multi-dimensional subject, it is better to use useful teaching materials to make teaching-learning activities effective, easy and long lasting.